Efficacy of topical clobetasol propionate in the treatment of idiopathic granulomatous mastitis - CÖMERT ÖZER, ELİF; UĞURLU, MUSTAFA ÜMİT (MARMARA UNIV, FAC MEDICINE, 2018)
Objectives: To evaluate the efficacy of topical clobetasol propionate 0.05% pomade in the treatment of idiopathic granulomatous mastitis. Patients and Methods: Twenty-one idiopathic granulomatous mastitis patients' clinical and histopathological fmdings were retrospectively reviewed. Those patients excluded from other etiologies were categorized as idiopathic granulomatous mastitis and treated with topical clobetasol propionate 0.05% pomade as an initial treatment. Results: All 21 patients with a fmal diagnosis of idiopathic granulomatous mastitis were women with the average age of 36.2+/-5.2 years. Of the 21 patients; erythema, induration and pain problems of 6 (28.5%) patients totally resolved without recurrence in 3 months follow-up period. Erythema, induration and pain problems of 7 (33.5%) patients were minimalized and stay stable in 3 months follow-up period. The symptoms of 8 (38%) did not change under topical clobetasol propionate treatment. None of the patients developed side or adverse effects due to topical steroid treatment and 6 of 18 patients with non-steroidal anti-inflammatory drugs (NSAIDs) complained of gastric pain. Conclusion:Topical steroid treatment is a safe treatment option for idiopathic granulomatous mastitis patients before systemic steroid and immunosuppressive treatments and also surgery.
Keywords: Idiopathic granulomatous mastitis; Granulomatous mastitis; Mastitis; Topical Steroid; Steroid; LOBULAR MASTITIS; MANAGEMENT; EXPERIENCE; STEROIDS; DISEASE